Handling Early Detection of Cervical Cancer on the Motivation of Women of Childbearing Age to Perform VIA Examinations in the Work Area of the Community Health Center - Nursiah, Andi; Saide, Rusnaeni; Dalle, Satiani; Hasiba, Hasiba; Bayuningrum, Pratiwi; Sudin, Sudin (International Journal of Health Sciences, 2024)
The incidence of cervical cancer in Indonesia in 2011 reached 100 per 100,000 population per year and the spread appears to be accumulating in Java and Bali. This figure is estimated to continue to increase by 25% in the next 10 years if preventive measures are not taken. Cervical cancer ranks second among all cancers in women with an incidence rate of 9.7 % and a death rate of 9.3% of all cancers in women in the world. Early detection of cervical cancer is an innovative breakthrough in health development to reduce mortality and morbidity due to cervical cancer. The aim is to determine the effect of health education regarding early detection of cervical ca on the motivation of women of childbearing age to undergo VIA examinations in the Antang Community Health Center working area. This type of research is research using an analytical survey method with a cross sectional study approach. With a population of 197 people and a sample size of 30 people with a sampling technique using purposive sampling. Data analysis was carried out using the Mc.Nemar Test. The results of the statistical test research on all respondents using the Mc. Nemar test obtained a p value of 0.000<p value 0.05. HO is rejected Ha is accepted, then there is an influence of Health Education regarding Early Detection of Cervical Ca on Women of Childbearing Age Carrying out IVA Examinations in the Antang Health Center Work Area.